2007
DOI: 10.1017/s0007114507837421
|View full text |Cite
|
Sign up to set email alerts
|

Walnut extract (Juglans regia L.) and its component ellagic acid exhibit anti-inflammatory activity in human aorta endothelial cells and osteoblastic activity in the cell line KS483

Abstract: Epidemiological studies suggest that the incidence of CVD and postmenopausal osteoporosis is low in the Mediterranean area, where herbs and nuts, among others, play an important role in nutrition. In the present study, we sought a role of walnuts (Juglans regia L.) in endothelial and bonecell function. As the endothelial cell expression of adhesion molecules has been recognised as an early step in inflammation and atherogenesis, we examined the effect of walnut methanolic extract and ellagic acid, one of its m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(121 citation statements)
references
References 60 publications
4
108
0
3
Order By: Relevance
“…Some studies suggested that walnut extracts have a high antiatherogenic potential and a remarkable osteoblastic activity, an effect mediated, at least in part, by its major component ellagic acid. Such findings implicate the beneficial effect of a walnut-enriched diet on cardioprotection and bone loss (Papoutsi et al 2008;Larrosa et al 2010).…”
Section: Determination Of 17 Phenolic Compounds In Walnut Leaves Extrmentioning
confidence: 73%
“…Some studies suggested that walnut extracts have a high antiatherogenic potential and a remarkable osteoblastic activity, an effect mediated, at least in part, by its major component ellagic acid. Such findings implicate the beneficial effect of a walnut-enriched diet on cardioprotection and bone loss (Papoutsi et al 2008;Larrosa et al 2010).…”
Section: Determination Of 17 Phenolic Compounds In Walnut Leaves Extrmentioning
confidence: 73%
“…First, as discussed, walnuts are the only nuts that contain substantial amounts of ALA, which is described as one of the more anti-inflammatory fatty acids [109,110]. And second, walnuts are also particularly rich in the phenolic compound ellagic acid, which has shown potent anti-inflammatory properties in experimental studies [111,112]. Nevertheless, plasma levels of CRP, a standard measure of systemic low-grade inflammation, were usually unaffected in controlled feeding trials with almonds, walnuts, or mixed nuts, as reviewed up to 2008 [21].…”
Section: Nut Feeding Trials With Outcomes On Cardiovascular Risk Fmentioning
confidence: 99%
“…Walnuts have more anti-inflammatory effects than other nuts for two reasons; Firstly, because they are the only nuts that contain substantial amounts of ALA, which is known as one of the more anti-inflammatory fatty acids [35,36], and secondly, they are also particularly rich in the phenolic ellagic acid, which has shown potent anti-inflammatory properties in experimental studies [37,38].…”
Section: Discussionmentioning
confidence: 99%